Social enterprise scaling up strategy – franchise development - Marta Ziółkowska (Studia i Materiały)
This paper is an exploratory study on the essence of social franchise as a business model and form of entrepreneurship and study how to use the proven business model to satisfy social needs. The paper is descriptive in nature and case study research approach has been used. The paper examines social franchising by analysing and exploring case studies of social enterprises. The study’s findings prove that franchise may be successfully applied in different dimensions of social entrepreneurship. It is concluded that the franchise model can be used as a tool to build socially sustainable societies and help to resolve the problem of social exclusion. Moreover, the study provides basic characteristics and knowledge for future in-depth research with regards to this topic.